MANAJEMEN PEMBELAJARAN COLLABORATIVE PADA MATERI MOMEN INERSIA DI SMA NEGERI 2 TONDANO - Paendong, Agritia Claudia; Rende, Jeane Cornelda; Komansilan, Alfrits (Charm Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to determine Collaborative Learning Management on Moment of Inertia material for class XI IPA SMA N Tondano. This research uses a mix method with a mixed combination model of two methods, namely qualitative and quantitative. Mixed Methods research is a new approach in research, although some researchers state that this research method is not a new approach in research. The subjects of this study were students of class XI IPA SMA N 2 Tondano. Retrieval of data in the form of test questions, interviews and documentation. The results showed the role of the components in the learning management function, namely the planning stage, the actuating stage, the organizing stage, and the controlling/evaluation stage. There was an increase in student learning outcomes after applying collaborative learning management in solving physics problems on the moment of inertia material at SMA N 2 Tondano.